Child Sexual Abuse History and Adult Promiscuity Among Female Filipino Survivors - Faith Frances Biado Miranda; Armina B Mangaoil; Teresita T Rungduin (Universitas Ahmad Dahlan, 2023)
This study explored the relationship of Childhood Sexual Abuse (CSA) and Adult Promiscuity among Filipina CSA survivors. It took into account the narratives of four participants who shared their experiences about being sexually abused as children, how the events affected them in youth into adulthood, their coping mechanisms, the seasons in their lives spent in promiscuity, and where they are now. Results showed that these survivors engaged in risky sexual activities because they wanted some semblance of control over what happened, they were addicted to the system of the abuse, and they were led to believe the negative notions instilled on their minds by their abusers. They were dissatisfied about their sexual experiences. Further into the paper, it was revealed that three out of these survivors no longer live promiscuous lives—where they expressed dissatisfaction with—and are either in recovery or had recovered from CSA. Cultural implications were also examined, showing that the Philippines has a secret pandemic of CSA, that its conservativeness attaches shame to CSA survivors, and that spirituality as Filipinos have both negative and positive effects amongst the lives of participants. In essence, this paper aims to assist with solutions to psychological problems of sexual trauma and the societal consequences they entail.Keywords: trauma, abuse, promiscuity, sexual abuse, childhood sexual abuse and adult promiscuity